2021
DOI: 10.1163/22134468-bja10033
|View full text |Cite
|
Sign up to set email alerts
|

Time Speeds Up During Flow States: A Study in Virtual Reality with the Video Game Thumper

Abstract: Flow is a mental state characterized by deep absorption during challenging activities, which was first studied by Mihaly Csikszentmihalyi. One of the defining characteristics of this state is the loss of the sense of time. Despite the widespread scientific interest in flow, there are few quantitative studies specifically on the aspect of time perception. The present study focuses on the relation between time perception and flow states in the context of video game play. Participants (n = 100) played the rhythm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 52 publications
5
33
0
Order By: Relevance
“…We appreciate the significance of time, especially in relation to the study of the aforementioned variables and their relationships (e.g., Figure 1 ). Our underlying premise, concurring in part with recent research development into the neuroscience of time and flow (e.g., Wittmann, 2011 ; Rutrecht et al, 2021 ), contends that time displacement could indeed function as a confounding factor, which then would account for a state of flow, personal experience of flourishing, and/or the operational mechanism of optimization ( Phan et al, 2019b ). Interestingly, in a recent study, Rutrecht et al (2021) found that time that time perception is intricately linked to flow states.…”
Section: Conceptualization: Theory Of Goals Of Best Practicesupporting
confidence: 60%
See 2 more Smart Citations
“…We appreciate the significance of time, especially in relation to the study of the aforementioned variables and their relationships (e.g., Figure 1 ). Our underlying premise, concurring in part with recent research development into the neuroscience of time and flow (e.g., Wittmann, 2011 ; Rutrecht et al, 2021 ), contends that time displacement could indeed function as a confounding factor, which then would account for a state of flow, personal experience of flourishing, and/or the operational mechanism of optimization ( Phan et al, 2019b ). Interestingly, in a recent study, Rutrecht et al (2021) found that time that time perception is intricately linked to flow states.…”
Section: Conceptualization: Theory Of Goals Of Best Practicesupporting
confidence: 60%
“…Our underlying premise, concurring in part with recent research development into the neuroscience of time and flow (e.g., Wittmann, 2011 ; Rutrecht et al, 2021 ), contends that time displacement could indeed function as a confounding factor, which then would account for a state of flow, personal experience of flourishing, and/or the operational mechanism of optimization ( Phan et al, 2019b ). Interestingly, in a recent study, Rutrecht et al (2021) found that time that time perception is intricately linked to flow states. Particularly, that the more flow someone experiences, the less they think about time, and the faster time passes for them.…”
Section: Conceptualization: Theory Of Goals Of Best Practicesupporting
confidence: 60%
See 1 more Smart Citation
“…The way that people perceive the speed of passing time would change according to the situation (e.g. time slowing in a waiting situation or flying when having fun) (Rutrecht et al, 2021;Witowska et al, 2020aWitowska et al, , 2020b. Similarly, the amount of time that people spend thinking about the past, present or future would also change according to context (e.g.…”
Section: Living Through a Pandemicmentioning
confidence: 99%
“…In a survey conducted by Wood et al (2007), 99% of respondents reported losing track of time while playing video games. A number of experimental studies also showed that we tend to underestimate the duration of a play session and experience a faster passage of time (Bisson et al, 2012;Bisson & Grondin, 2013;Luthman et al, 2009;Rau et al, 2006;Rutrecht et al, 2021;Tobin et al, 2010;Tobin & Grondin, 2009;Wood et al, 2004). This relates directly to the mental state called flow Csikszentmihalyi, 2009Csikszentmihalyi, , 2014, which is characterized by deep absorption in an activity, a sense of control, and the loss of the senses of self and time (Wittmann, 2015(Wittmann, , 2018.…”
mentioning
confidence: 99%